PREVENTING SCHOOL VIOLENCE AMONG ADOLESCENTS THROUGH SOCIALIZATION AND PSYCHOLOGICAL FIRST AID (PFA) AT SMA NEGERI 1 GENTENG BANYUWANGI: CEGAH PERILAKU KEKERASAN PADA REMAJA MELALUI SOSIALISASI DI SMA N 1 GENTENG BANYUWANGI - Intan Fitranisa; Dwi Retna Kumalaningrum; Firtha Ayu Rachmasari; Bella Amanda (Universitas Airlangga, 2026)
Violence in educational settings represents a critical issue that negatively affects adolescents’ psychological well-being, social functioning, and educational continuity. Such incidents frequently remain underreported due to limited self-protection literacy and inadequate psychosocial safety within school environments. This community engagement program aimed to identify the forms of violence experienced by students, analyze factors underlying reluctance to report incidents, and enhance violence prevention awareness through the integration of regulatory-based socialization and Psychological First Aid (PFA). The program was implemented at SMA Negeri 1 Genteng Banyuwangi and involved 100 students, utilizing a pre-intervention descriptive quantitative survey, followed by violence prevention socialization aligned with the Regulation of the Minister of Education, Culture, Research, and Technology Number 46 of 2023, as well as basic PFA training. The findings indicated that 36.6% of students had experienced violence, predominantly verbal and psychological forms such as catcalling, bullying, and violations of personal boundaries. Reluctance to report incidents was mainly attributed to fear of negative social consequences, the persistence of a victim-blaming culture, and limited trust in school reporting mechanisms. The integration of regulatory socialization and PFA is therefore recommended as a sustainable approach to improving violence-related literacy, strengthening psychosocial safety, and fostering a safe and supportive school environment.